Notes on the genus Gymneia (Lamiaceae: Ocimeae, Hyptidinae) with two new species from Brazil - Harley, R.m. (Phytotaxa, 2013)
Two new species of Gymneia from Brazil, G. moniliformis and G. chapadensis are described and illustrated, and details of habitat and conservation status included. Morphological relationships to other species of the genus are given, and inflorescence structure of the genus discussed.